“Into her Dream he Melted”: Women Artists Remodelling Keats - Wootton, Sarah (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2008)
AbstractThis essay examines the central role of women in modelling Keats’s posthumous reputation during the late nineteenth and early twentieth centuries by focusing on the visual heritage of his narrative poems. While the Pre-Raphaelite’s interest in and well-known renderings of Keats’s poems have been the subject of previous critical attention, many comparable images by women artists have been neglected. This essay analyses a wide variety of paintings, drawings and illustrations based on Keats’s “Isabella; or, the Pot of Basil” and “La Belle Dame sans Merci” by women artists at the turn-of-the-century. This examination of women artists, who were celebrated during their own lifetimes but are now virtually forgotten, culminates in a detailed discussion of Jessie Marion King. Her highly innovative illustrations for Keats’s poetry are not only indicative of the final phase of Pre-Raphaelitism and the distinctive “Glasgow Style;” they also underline the significance of women’s artistic responses to literature during this period.